ANALISIS KESALAHAN ÉJAAN BAHASA BALI LATIN PADA FANPAGE PENYULUH BAHASA BALI KABUPATEN BANGLI - Kadek Ambarwati; I Kadek Widiantana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Analysis of writing errors in The Latin Balinese language is very important to do, especially for writings uploaded on digital media such as the Balinese Language Extension Fanpage of Bangli Regency which can be easily accessed and disseminated. This study examined the form of Latin Balinese language errors on the Balinese Language Extension Fanpage of Bangli Regency; Factors that caused the occurrence of Latin Balinese language errors on the Balinese Language Extension Fanpage of Bangli Regency; and efforts that can be made to minimize the occurrence of Writing errors in Balinese Latin on the Fanpage of Balinese Language Extension Workers of Bangli Regency. The theories used in this study are the theory of language error analysis and the theory of motivation. This type of research is descriptive research using a qualitative approach. The data collection technique in this study used interview techniques and document studies. The collected data is analyzed through data reduction, data presentation, and then drawing conclusions. The results showed: (1) The form of Latin Balinese language errors on the Fanpage of the Balinese Language Extension Officer of Bangli Regency, namely: (a) Capital letter writing errors, (b) Letter writing errors, (c) Preposition writing errors, (d) Pronoun writing errors, (e) Italic writing errors, (f) Punctuation errors. (2) Factors causing errors in Latin Balinese, namely: (a) Mistake factors,(b) Error factors (human error and technological errors). (3) Efforts to minimize errors in the writing of Balinese Latin, namely: (1) Efforts to minimize human error, (2) Efforts to minimize technological errors.